DNA charge neutralization by linear polymers: irreversible binding. - Maltsev, E; Wattis, J; Byrne, H (2006)
We develop a deterministic mathematical model to describe the way in which polymers bind to DNA by considering the dynamics of the gap distribution that forms when polymers bind to a DNA plasmid. In so doing, we generalize existing theory to account for overlaps and binding cooperativity whereby the polymer binding rate depends on the size of the overlap. The proposed mean-field models are then solved using a combination of numerical and asymptotic methods. We find that overlaps lead to higher coverage and hence higher charge neutralizations, results which are more in line with recent experimental observations. Our work has applications to gene therapy where polymers are used to neutralize the negative charges of the DNA phosphate backbone, allowing condensation prior to delivery into the nucleus of an abnormal cell.